Education Values in the Traditional Clothing of Panaragan Javanese Society: a Study of Semiotics - Sugianto, Alip; Abdullah, Wakit; Sumarlam, Sumarlam; Teguh Widodo, Sahid (Opción, 2019)
Tradisional clothing is an identity of a society. It keeps a million meanings, values and world views of the society. The values contained in traditional clothing need to be revealed to build a more civilized society. Data collec- tion was carried out with a method of observing and competing in the field with warok Ponorogo figures. Data analysis using a semiotic approach towards traditional clothing of Ponorogo. The results of this study indicate that the traditional clothes have education values found in traditional clothing. These Education values include religious education, cultural education, social education, and economic education.